Internalization of Pancasila Students' Profile values through Al-Qur'an Hadith materials in tenth grade at SMKN 8 Surabaya - Siswanto, Shofiyah Salsabila; Asrori, Asrori; Rusman, Rusman (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This research aimed to understand the concept of the Pancasila students' profile and the process of internalizing its ethical values through Al-Qur'an Hadith materials in SMKN 8 Surabaya. Furthermore, it used descriptive qualitative methods with field research types to obtain accurate data through conducting observations, interviews, and documentation as techniques for collecting data related to internalizing Pancasila students' profile values. The results showed the six dimensions of Pancasila students' profile, namely 1) having a belief in God and a noble character, 2) promoting global tolerance, 3) fostering cooperation, 4) promoting self-reliance, 5) developing critical thinking, and 6) promoting creativity. In her role as a teacher of Islamic Education, Mrs. Himma consciously incorporated these aspects into her teaching materials to instill the values of the Pancasila Students' Profile among Tenth Grade students through the study of Al-Qur'an Hadith.